Nordihydroguaiaretic acid recovery from Larrea tridentata by microwave-assisted extraction - Martins, Sílvia (2010)
Nordihydroguaiaretic acid (NDGA) is a powerful antioxidant with biological activities of great interest in several health areas, including antiviral, cancer chemopreventive, and antitumorgenic. Little information is available on extraction methods of NDGA from Larrea tridentata. Hence, the aim of this study was to develop a rapid and effective microwave-assisted extraction (MAE) method for NDGA recovery from Larrea tridentata leaves, and to compare the results obtained with those found using conventional heatreflux extraction (HRE).